ULK1 ubiquitylation is regulated by phosphorylation on its carboxy terminus - Nazio, Francesca (Cell Cycle, 2017)
Autophagy is a highly conserved process that acts sequestering cytoplasmic components for their degradation by the lysosomes. It consists of several sequential steps that have to be finely regulated to ensure both its progression and termination. Post-translational modifications (PTMs) play an important role in regulating ATG proteins function in different stages of autophagy. Recently, we demonstrated that, during prolonged starvation, ULK1 protein is specifically ubiquitylated by NEDD4L, and that this regulation is important to protect cells against excessive autophagy. In this Extra view, we show that ULK1 phosphorylation at 3 different sites on the same ULK1 target region for NEDD4L is preparatory for its ubiquitylation and subsequent degradation. This adds to the complexity of ULK1 multi-level regulation by several factors, including kinases, phosphatases and acetylases, with each contributing to autophagy homeostasis